The postoperative part of perioperative chemotherapy fails to provide a survival benefit in completely resected esophagogastric adenocarcinoma - Peters, Leila; Blank, Susanne; Nienhüser, Henrik; Haag, Georg Martin; Jäger, Dirk; Bruckner, Thomas; Schmidt, Thomas; Ulrich, Alexis (Surgical oncology, 2017)
BACKGROUND: Based on two benchmark studies perioperative chemotherapy (CTx) has become standard treatment for locally advanced esophagogastric adenocarcinoma (EGA) in Europe. However, only half of the patients in both studies actually received postoperative CTx (aCTx). Thus, we evaluated the prognostic impact of preoperative CTx (nCTx) and aCTx combined versus nCTx alone. Furthermore, we aimed to identify subgroups potentially beneficial of aCTx and factors associated with its non-administration. - METHODS: We retrospectively analyzed 299 consecutive patients with EGA, who underwent complete resection (all M0, R0) after nCTx in our institution and were eligible for aCTx. Patients with and without aCTx were compared regarding clinicopathological data, treatment, morbidity, and long-term prognosis. - RESULTS: 129 patients (43.1%) did not receive aCTx. Administration of aCTx did not significantly improve overall (OS) and recurrence free survival (RFS) (median OS: 78.2 months vs. not reached, p = 0.331; RFS: 43.3 vs. 41.1 months, p = 0.118), but was an independent positive predictor of RFS (HR 1.6 95%CI 1.1-2.5, p = 0.024). aCTx improved RFS in non-intestinal tumors (p = 0.023) and patients receiving FLOT regimen (p = 0.038). By logistic regression analysis factors predictive of non-administration of aCTx were older age (>65 years: OR 3.2, p = 0.028), longer hospital stay (15-28 days: OR 2.6, p = 0.001; >28 days: OR 5.2, p < 0.001), and histopathologic non-response (OR 1.9, p = 0.023). - CONCLUSION: Advanced age, histopathologic non-response, and prolonged convalescence due to postoperative morbidity lead to omission of aCTx. However, this study could not provide evidence to support the beneficial role of aCTx in perioperative chemotherapy regimens for a selected patient collective with EGA and excellent prognosis.
In Press, Corrected Proof
Gesehen am 08.07.2019